Bibliometrix Analysis: Management Inventory dan Supply Management - Hariyanto Hariyanto; Riki Riki (Komunitas Dosen Indonesia, 2023)
Inventory and Supply Management is an important aspect of efficient business operations. Both are interrelated and have an impact on achieving competitive advantage and customer satisfaction. In the case study of PT. Berkahjaya Sentosa Technique, Bibliometrix analysis is used to evaluate the performance of inventory and supply management of companies. The results show that effective inventory and supply management can improve operational efficiency and customer satisfaction. Bibliometrics is an analytical method used to map and analyze scientific literature in a particular field. In the context of inventory management and distribution control, bibliometrics can provide valuable insight into the development and focus of study in a particular field. The purpose of this study is to analyze and summarize scientific literature related to inventory management and distribution control using bibliometric methods. The method used is descriptive analysis using analysis tools such as three-field plots and tables of main information. The results show that scientific literature related to inventory management and distribution control has experienced a decline in annual growth in the period 2018-2023. However, the average citation per document shows that this literature is still very relevant and important in the context of inventory management and distribution control. This research provides valuable insights for researchers and practitioners in the field of inventory management and distribution control